Studying of high pressure/deep formations based on rock mechanical properties evaluation - Bandar, Muayad Khalaf; Al- Ameri, Nagham Jasim (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
Geomechanics plays a significant role in all phases of an oil and gas field’s life cycle, from exploration to production and even beyond field abandonment. It has various applications in the petroleum industry, such as predicting safe mud window and determining the magnitude and direction of in-situ stresses. The objective of this study is to determine the magnitude and orientation of far-field stresses, identify fault types, estimate pore pressure, and evaluate mechanical properties for different formations by constructing a one-dimensional geomechanical model (1D-MEM) for a deep well in the Halfaya oilfield. This study utilizes open-hole log measurements, including density, sonic compression and shear wave velocities, gamma-ray, caliper, and bit size. The results from the model indicate that the Mishrif A, Mishrif B1, Mishrif B2, Mishrif C1, Mishrif C2, Mishrif C3, Mauddud, Nahr Umr B, Ahmadi, and Zubair formations exhibit normal faulting. On the other hand, the Nahr Umr A, Shuaiba, Ratawi, and Yamama formations show strike-slip faulting. The Rumaila formation, based on the magnitudes of the far-field stresses, appears to exhibit reverse faulting. Furthermore, the Yamama formation demonstrates abnormally high pore pressure, while other formations are considered natural pressure formations. In terms of rock properties, shale and sand formations have lower Young’s modulus, Poisson’s ratio, and UCS, whereas limestone formations have higher values. Moreover, limestone formations exhibit higher friction angles compared to sandstone and shale formations.